Integrated dataset of screening hits against multiple neglected disease pathogens. - Solomon Nwaka; Dominique Besson; Bernadette Ramirez; Louis Maes; An Matheeussen; Quentin Bickle; Nuha R Mansour; Fouad Yousif; Simon Townson; Suzanne Gokool; Fidelis Cho-Ngwa; Moses Samje; et al. (Public Library of Science (PLoS), 2011)
New chemical entities are desperately needed that overcome the limitations of existing drugs for neglected diseases. Screening a diverse library of 10,000 drug-like compounds against 7 neglected disease pathogens resulted in an integrated dataset of 744 hits. We discuss the prioritization of these hits for each pathogen and the strong correlation observed between compounds active against more than two pathogens and mammalian cell toxicity. Our work suggests that the efficiency of early drug discovery for neglected diseases can be enhanced through a collaborative, multi-pathogen approach.